Access to justice, digitalization and vulnerability exploring trust in justice - Creutzfeldt, Naomi 1974-; Kyprianides, Arabella; Jackson, Jonathan 1974-; Bradford, Ben (Bristol University Press, 2024)
Written by key names in the field, this book explores the impact of digitization and COVID-19 on justice in housing and special needs education. It analyses access to justice, offers recommendations for improvement and provides valuable insights into administrative justice from user perspectives
Title from publisher's bibliographic system (viewed on 10 Jan 2025)
1: Legal Needs and Access to Justice -- 2: Trust in Administrative Justice -- 3: Two Areas of Law in Context and the Help-Seeker Journey -- 4: Pathways through the AJS -- Housing -- 5: Pathways through the AJS -- SEND -- 6: Exploring the Role of Procedural Justice in Tribunals and Ombuds -- 7: Access to Digital Justice -- 8: Marginalized Groups and Unmet Legal Needs
Keywords: Justice, Administration of / Technological innovations / England; Justice, Administration of / Technological innovations / Wales; Special education / Law and legislation / England; Special education / Law and legislation / Wales; Trust